A mysterious something in the light : the life of Raymond Chandler - Williams, Tom, 1981- (Chicago Review Press, 2013)
The life of Raymond Chandler has long been obscured by secrets and half-truths as deceptive as anything in his novel The Long Goodbye. Now, drawing on new interviews, previously unpublished letters, and archives on both sides of the Atlantic, Tom Williams casts a new light on this most mysterious of writers. The Raymond Chandler revealed is a man troubled by loneliness and desertion from an early age.